2012
DOI: 10.1007/s12272-012-0617-6
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of rutin against ischemia/reperfusion-associated hemodynamic alteration through antioxidant activity

Abstract: Reactive oxygen species exert toxic effects during ischemia-reperfusion (I/R) injury of various organs. This study was designed to evaluate the preventive effects of various isoflavonoids such as biochanin A, daidzein, genistein, rutin and quercetin. These compounds are wellknown naturally occurring compounds with beneficial health effects and antioxidant activity. Free radical scavenging activity was measured by 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay and superoxide dismutase (SOD) assay. Among the isoflav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…This indicates that influence of rutin on photochemical GFP behavior is mediated by intracellular biochemical pathways. Rutin and its analogs were previously described as efficient scavengers of radicals [9], [10]. In addition, it was recently demonstrated that rutin reacts with light-excited flavins [11].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that influence of rutin on photochemical GFP behavior is mediated by intracellular biochemical pathways. Rutin and its analogs were previously described as efficient scavengers of radicals [9], [10]. In addition, it was recently demonstrated that rutin reacts with light-excited flavins [11].…”
Section: Resultsmentioning
confidence: 99%
“…SOD and CAT are major antioxidant enzymes, which are involved in protective effects in organ injury. In ischemia/reperfusionassociated hemodynamic alteration, rutin improves left ventricular end diastolic pressure by enhancing the antioxidant enzyme SOD activity (Bhandary et al, 2012). In addition, rutin has protective effects in amylin-induced neurocytotoxicity by increasing the activity of CAT, which suggests that rutin can be used as a feasible agent to protect the aging brain (Yu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In rats fed a high carbohydrate and fat diet, rutin attenuated metabolic changes and cardiac remodeling [ 56 ]. In control and diabetic rats, rutin had a cardioprotective role against ischaemia–reperfusion injury [ 16 , 57 ]. In a clinical setting, this flavonoid decreased systemic blood pressure in diabetic patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%